Hubungan Pengetahuan Ibu Hamil tentang Anemia dengan Kepatuhan Konsumsi Tablet Fe di Puskesmas Jambo Aye Aceh Utara Tahun 2024 - Rosnidar Rosnidar; Ester Simanullang; Yasrida Nadeak (Inovasi Kesehatan Global, 2025)
Pregnancy with anemia can pose a danger to the mother and child, so it is a risky condition for pregnant women and requires special medical attention. The aim of this study was to determine the relationship between third trimester pregnant women's knowledge about anemia and compliance with taking Fe tablets at the Jambo Aye Health Center, North Aceh. This type of research is an analytical survey using a cross-sectional research design. Samples were taken from the entire population of Jambo Aye Community Health Center. A total of 32 pregnant women in the third trimester from January to June 2024. The results of the square test analysis show that the p value = 0.000 which means less than A = 0.005, so it can be concluded that there is a significant relationship between knowledge of third trimester pregnant women about anemia and compliance with consuming Fe tablets. at the Tanah Jambo Aye North Aceh Health Center in 2024. Through this research, it can provide information to the Tanah Jambo Aye North Aceh Health Center about awareness among pregnant women of anemia and Compliance with consuming Fe tablets to prevent anemia during pregnancy.